1995
DOI: 10.1002/bjs.1800821121
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of a prospective randomized study of endoscopic versus surgical treatment of bile duct calculi in patients with gallbladder in situ

Abstract: Eighty-three patients with bile duct calculi were entered in a prospective randomized study of endoscopic sphincterotomy (ES) and stone removal (group 1) versus surgery alone (group 2), and were followed for more than 5 years. In group 1 endoscopic stone clearance was successful in 35 of 39 patients. Thirteen patients subsequently had cholecystectomy with (n = 7) or without (n = 6) biliary symptoms and one had a cholecystostomy for acute cholecystitis. Two patients have had mild biliary colic or pancreatitis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 43 publications
1
57
0
3
Order By: Relevance
“…The answer is not straightforward. McAlister et al performed a metaanalysis that included five prospective randomized trials [9,[80][81][82][83] showing the benefit of an additional cholecystectomy after ES in case of symptomatic gallstone diseases, including ABP [84]. An additional cholecystectomy resulted in a lower death rate (7.9% vs 14.1%; p = 0.01) even in studies that included patients from higher-risk American Society of Anesthesiology (ASA) classes.…”
Section: Endoscopic Sphincterotomy Versus Conservative Managementmentioning
confidence: 99%
“…The answer is not straightforward. McAlister et al performed a metaanalysis that included five prospective randomized trials [9,[80][81][82][83] showing the benefit of an additional cholecystectomy after ES in case of symptomatic gallstone diseases, including ABP [84]. An additional cholecystectomy resulted in a lower death rate (7.9% vs 14.1%; p = 0.01) even in studies that included patients from higher-risk American Society of Anesthesiology (ASA) classes.…”
Section: Endoscopic Sphincterotomy Versus Conservative Managementmentioning
confidence: 99%
“…9 Hammarstrom et al also found both procedures equally effective in the elderly in the long term, though suggesting surgery to be the better option due to significantly increased mortality from heart disease in those having ERCP compared to cholecystectomy. 10 Minimal intervention utilising percutaneous cholecystostomy (PC) has been suggested as a suitable alternative to cholecystectomy in the critically ill patient. It has a low procedure-related morbidity and mortality, and the literature available suggests that there is early resolution of acute symptoms.…”
mentioning
confidence: 99%
“…The percentage of retained stones only 1% -3%, and during long-term followup revisional surgery was necessary in about 10% of the patients. [2][3][4][5] With the advent of minimal access surgical techniques and endoscopic access to our armamentarium, the modern surgeons' experience with the traditional open CBD exploration is fast decreasing.…”
Section: Discussionmentioning
confidence: 99%